Predictors of Academic Neurosurgical Career Trajectory among International Medical Graduates Training Within the United States. Issue 3 (September 2021) - Khalafallah, Adham M; Jimenez, Adrian E; Camp, Samantha; Horowitz, Melanie A; Chiu, Ian; Ryu, David; Charewycz, Natasha; Vera, Lauren; Bhoopalam, Myan; Feghali, James; Sharma, Mayur; Lubelski, Daniel; et al.
Abstract : BACKGROUND : Within the literature, there has been limited research tracking the career trajectories of international medical graduates (IMGs) following residency training. OBJECTIVE : To compare the characteristics of IMG and US medical school graduate (USMG) neurosurgeons holding academic positions in the United States and also analyze factors that influence IMG career trajectories following US‐based residency training. METHODS : We collected data on 243 IMGs and 2506 USMGs who graduated from Accreditation Council for Graduate Medical Education (ACGME)‐accredited neurosurgery residency programs. We assessed for significant differences between cohorts, and a logistic regression model was used for the outcome of academic career trajectory. RESULTS : Among the 2749 neurosurgeons in our study, IMGs were more likely to pursue academic neurosurgery careers relative to USMGs (59.7% vs 51.1%; P = .011) and were also more likely to complete a research fellowship before beginning residency (odds ratio [OR] = 9.19; P < .0001). Among current US academic neurosurgeons, USMGs had significantly higher pre‐residency h‐indices relative to IMGs (1.23 vs 1.01; P < .0001) with no significant differences between cohorts when comparing h‐indices during (USMG = 5.02, IMG = 4.80; P = .67) or after (USMG = 14.05, IMG = 13.90; P = .72) residency. Completion of a post‐residency clinical fellowship was the only factor independently associated with an academic career trajectory among IMGs (OR = 1.73, P = .046). CONCLUSION : Our study suggests that while IMGs begin their US residency training with different research backgrounds and achievements relative to USMG counterparts, they attain similar levels of academic productivity following residency. Furthermore, IMGs are more likely to pursue academic careers relative to USMGs. Our work may be useful for better understanding IMG career trajectories following US‐based neurosurgery residency training.